2012
DOI: 10.1542/peds.2011-1111
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Immune Thrombocytopenic Purpura After Vaccination in Children and Adolescents

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Studies on vaccine safety are crucial to the ongoing success of our national immunization program. ITP has a known association with MMR in young children, occurring in 1 in 40 000 doses. The risk after other childhood vaccines is unknown. WHAT THIS STUDY ADDS:This study found no increased risk of ITP after vaccines other than MMR in young children, confirmed an association of ITP with MMR, and also found that ITP may occur after certain other vaccines in older children.abstract BA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 40 publications
2
57
0
Order By: Relevance
“…The similarly elevated risk for ITP after either vaccine is consistent with previous studies which found increased ITP risk after MMR in children. [8][9][10] To our knowledge, the present study represents the first report that MMRV is associated with a similar increased risk of ITP during the same postvaccination risk intervals as MMR.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The similarly elevated risk for ITP after either vaccine is consistent with previous studies which found increased ITP risk after MMR in children. [8][9][10] To our knowledge, the present study represents the first report that MMRV is associated with a similar increased risk of ITP during the same postvaccination risk intervals as MMR.…”
Section: Discussionsupporting
confidence: 55%
“…The measles-mumps-rubella (MMR) vaccine has been associated with several safety outcomes, including febrile seizures, [1][2][3][4] fever, [5][6][7] immune thrombocytopenia purpura (ITP), [8][9][10] anaphylaxis, [11][12][13] and possibly arthritis/arthralgia. 14 After licensure of the combination measles-mumpsrubella-varicella vaccine (MMRV), the Advisory Committee on Immunization Practices recommended in 2006 that it preferred use of the MMRV over separate MMR and varicella (V) vaccines for the 2 recommended doses at 12 to 15 months and 4 to 6 years of age.…”
mentioning
confidence: 99%
“…"We can update these databases weekly, and thus virtually conduct real-time monitoring when a new vaccine is introduced, " says Frank DeStefano, director of the CDC's Immunization Safety Office. Data from the VSD helped disprove the connection between MMR and autism, but have also identified real adverse events, such as when 197 children in a cohort of 1.8 million who had received the MMR vaccination developed immune thrombocytopaenic purpura 4 . "It's a relatively benign blood disorder where there's easy bruising and bleeding, but it can be scary, " says Jason Glanz, an epidemiologist affiliated with the VSD at the Kaiser Permanente Institute for Health Research in Denver, Colorado.…”
Section: An Injection Of Trustmentioning
confidence: 99%
“…The incidence of ITP is estimated at 50-100 new cases per million per year (6,7). ITP in children is usually self-limiting, with a typically acute onset and frequently occurring a few days or weeks after viral infection or vaccination (8)(9)(10)(11)(12). At least 70 percent of childhood cases will end up in remission within six months, even without treatment (7,(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Acute ITP was considered to be associated with the use of a vaccine in case there was no recognized etiology and the interval between vaccination and onset of acute ITP symptoms was within 5 weeks (19). However, none of the routine childhood vaccines given in the first year of life was known to be significantly associated with an increased risk of ITP (20). Studies reporting a link between MMR vaccination and ITP have been criticized because concomitant viral infections have not usually been excluded.…”
Section: Introductionmentioning
confidence: 99%